Electrode configurations in atmospheric pressure plasma jets: production of reactive species. (30th October 2018) - Lietz, Amanda M; Kushner, Mark J
Abstract: Atmospheric pressure plasma jets (APPJs) are a preferred plasma source for many biomedical applications. These jets typically consist of a rare gas flowing through a dielectric tube, possibly with an O2 or H2 O admixture, and flowing into the ambient. They are typically powered by pulsed or sinusoidal voltage waveforms. However, in most other aspects APPJ designs differ greatly. In this paper, APPJ design parameters and their consequences on ionization wave (IW) propagation and reactive oxygen and nitrogen species (RONS) production are discussed using results from a two-dimensional plasma hydrodynamics model. The base case is an APPJ with a single powered ring electrode wrapped around a dielectric tube. This configuration was varied by adding a grounded ring electrode, changing the powered and grounded electrode positions, and moving the powered electrode to the inside of the tube. Placing the powered electrode closer to the outlet of the tube increased the RONS production by increasing the energy deposition outside the tube. Adding a grounded ring increased the IW intensity inside the tube while slightly increasing the power deposition outside of the tube. An inner powered electrode increased the IW intensity and propagation velocity, and the resulting RONS production. Co-axial ground planes within 5 cm of the APPJ significantly affected the IW behavior, increasing its intensity and increasing RONS production. The consequences of voltage rise time and dielectric constant of the tube are also discussed. The systematic trends from this investigation may facilitate more informed APPJ design choices that may be tailored to the goals of a specific application.